2021
DOI: 10.1097/md.0000000000027678
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture combined with traditional Chinese medicine on chronic prostatitis

Abstract: Background: Chronic prostatitis is a common andrological disease, which brings many troubles to the lives of middle-aged and elderly male patients. With the increase of modern life pressure, the incidence of chronic prostatitis tends to younger, but its etiology and pathogenesis are not fully elucidated. Which seriously affects men's health? Relevant studies have shown that acupuncture combined with traditional Chinese medicine (TCM) has a good effect on the treatment of chronic prostatitis compared with conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of the three groups of follow-up showed that the levels of tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin-12 (IL-12), prostate volume and prostate transition zone volume in groups A and B were significantly lower than those in group C (P<0.05), and AFR and MFR were significantly higher than before (P<0.05). Ma Yong et al [10] used acupuncture combined with traditional Chinese medicine to treat 30 patients with CP / CPPS of damp-heat stasis type, and the other 30 patients were treated with tamsulosin hydrochloride capsules.The results showed that after treatment, the NIH-CPSI score, Self-rating Anxiety Scale (SAS) score and Self-rating Depression Scale (SDS) score of the acupuncture-medicine group were better than those of the western medicine group (P<0.05). The improvement of clinical symptoms in the acupuncture-medicine group was significantly better than that in the western medicine group (P<0.05).…”
Section: Filiform Needle Combined With Drugsmentioning
confidence: 99%
“…The results of the three groups of follow-up showed that the levels of tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin-12 (IL-12), prostate volume and prostate transition zone volume in groups A and B were significantly lower than those in group C (P<0.05), and AFR and MFR were significantly higher than before (P<0.05). Ma Yong et al [10] used acupuncture combined with traditional Chinese medicine to treat 30 patients with CP / CPPS of damp-heat stasis type, and the other 30 patients were treated with tamsulosin hydrochloride capsules.The results showed that after treatment, the NIH-CPSI score, Self-rating Anxiety Scale (SAS) score and Self-rating Depression Scale (SDS) score of the acupuncture-medicine group were better than those of the western medicine group (P<0.05). The improvement of clinical symptoms in the acupuncture-medicine group was significantly better than that in the western medicine group (P<0.05).…”
Section: Filiform Needle Combined With Drugsmentioning
confidence: 99%